Physiological Responses of Laying Hens to the Alternative Housing Systems - Shini, Shaniko (International Journal of Poultry Science, 2003)
Measurements of differential leucocyte count, H/L (Heterophil to Lymphocyte) ratio and Ab (Antibody) titres to commercial used vaccines, ND (Newcastle Disease) and IB (Infectious Bronchitis) were employed to investigate whether the exposure of laying hens to different housing systems was associated with haematological-immunological changes. Layers were kept in three different housing systems: conventional battery cages, modified cages and an intensive free-range housing system. Differential leucocyte count and H/L ratio were used as indicators of stress response and sensitive biomarkers crucial to immune function, whereas the Ab levels to IB and ND vaccines were measured to assess humoral-mediated immunity. This study indicated that in hens exposed to the three various housing conditions H/L ratio was found to be significantly different, 0.58, 0.43 and 0.38, respectively. The results show that in hens kept in battery cages heterophils were raised, while lymphocytes decreased. Although, differences in H/L ratio suggest that hens of different housing systems should have a reduced antibody response and several investigators have recommended that environmental stressors decrease Ab production this was not demonstrated in this survey. Ab titre presented as log10 was unaffected by any housing system. A slight negative correlation between H/L ratios and antibody levels was also observed. The results would suggest that housing conditions and social stress might have a great effect on the stress response (H/L ratio) while humoral response seems unaltered.